Melt instabilities on semiconductor surfaces induced by laser radiation - Bonchik, A.Yu.; Dacko, B.J.; Demchuk, V.I.; Kiyak, S.G.; Palyvoda, I.P.; Shnyr, A.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Laser modifications of semiconductors are often realized by pulsed rapid melting and subsequent resolidification. Recently melt instabilities have been discovered in locally melted semiconductor surfaces. We determined that spontaneous segregation of uniform temperature stage of crystal lattice and charge carrier concentration can take place in electron-hole plasma, generated by laser radiation. Besides, there exists a positive feedback between the temperature of crystal lattice and charge carrier concentration in the region of their fluctuation. It causes both amplification of original fluctuation of temperature and generation of quasi-periodic temperature fields of large amplitude in semiconductors. The nonuniform temperature fields determine the features of surface relief formation in a zone of laser radiation action.